Immunotoxicity, immune dysfunction, and chronic disease - Luebke, Robert W.; Dietert, Rodney R. (Molecular and Integrative Toxicology, 2012)
Immunotoxicity, Immune Dysfunction, and Chronic Disease is among the first books to illustrate the linkage between environmental risk factors (e.g., chemicals, drugs, diet, lifestyles), environmentally-induced immune dysfunction and the full range of resulting chronic diseases and conditions. There is a detailed discussion of specific immune-based chronic diseases and conditions that emerge in children and adults and affect different physiological systems. The book integrates a consideration of risk factors and specific immunotoxic alterations with disease outcomes. A significant number of diseases and conditions are discussed, such as systemic allergic diseases affecting the lung, skin and gastrointestinal tract, systemic autoimmune diseases (type 1 diabetes,multiple sclerosis and lupus) and chronic conditions that are not traditionally associated with chemically-mediated immunomodulation (depression, frailty, and atherosclerosis). Inflammatory dysregulation is a common thread that connects many of the diseases and conditions discussed in this book and provides a central focus.  Individual chapters are organized by disease with the addition of chapters that provide integrative information on: 1) patterns of disease comorbidities and 2) the safety testing of chemicals and drugs to reduce the risk of immune dysfunction.  Each chapter contains a summary of key points as well as recommendations when appropriate. The book stresses the benefits of identifying the environmental risk factors of immune-mediated chronic disease and the potential to reduce the prevalence of these diseases and conditions.  This volume is a valuable resource for researchers, clinicians, risk assessors and regulators and students.